Effective time management skills increase your productivity and efficiency - Newbold, Curtis (O'Reilly Media, Inc., 2025)
Professionals often find their time and energy being stretched across countless projects and activities. Because of the many disparate day-to-day tasks they are faced with, they often struggle to streamline their schedules in ways that allow them to strategically accomplish what is most important. This course provides actionable time management tips for determining and setting goals; prioritizing tasks; and using assertiveness and delegation to increase your workplace efficiency and productivity.
Online resource; title from title details screen (O'Reilly, viewed January 21, 2025)
Keywords: Time management; Gestion du temps; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet